Multisectoral behavior change intervention improves diet quality, but not food security, in rural Uganda - Regina Brown; Stacy Griswold; Carolyn Van Sant; Ian Moore; Yanlin Ren; Gloria Desire Kayo; Jackson Bagabirwa; Merry Fitzpatrick; Anastasia Marshak; Marlene Hebie; Hugo De Groote; Patrick Webb; et al. (Global Food Security, 2024)

Equivalent roles of marine subsidies and island characteristics in shaping island bird communities - Debora S. Obrist; Patrick J. Hanly; Jeremiah C. Kennedy; Owen T. Fitzpatrick; Sara B. Wickham; Wiebe Nijland; Luba Y. Reshitnyk; Chris T. Darimont; Brian M. Starzomski; John D. Reynolds (Journal of Biogeography, 2024)
Aim Species distributions across islands are shaped by dispersal limitations, environmental filters and biotic interactions but the relative influence of each of these processes has rarely been assessed. Here, we examine the relative contributions of island characteristics, marine subsidies, species traits, and species interactions on avian community composition. Location Central Coast region of British Columbia, Canada. Taxon Terrestrial breeding birds. Methods We observed 3610 individuals of 32 bird species on 89 islands that spanned multiple orders of magnitude in area (0.0002–3 km 2 ). We fit a spatially explicit joint species distribution model to estimate the relative contributions of island physical characteristics, island‐specific inputs of marine subsidies, species' traits, and biotic interactions on species distributions. Biogeographic characteristics included island area, isolation, and habitat heterogeneity, while marine influence was represented by forest‐edge soil δ 15 N, wrack biomass, shoreline substrate, and distance to shore. This approach also allowed us to estimate how much variation in distributions resulted from species' biological traits (i.e. body mass, feeding guild, feeding height, and nesting height). Results Bird species distributions were determined almost equivalently by island biogeographic characteristics (23.5% of variation explained) and marine influence (24.8%). We detected variation in species‐specific responses to both island biogeographic characteristics and marine influence, but no significant effect of any biological trait examined. Additionally, we found evidence that habitat preferences were a more important driver than competitive interactions. Main Conclusions Although most island biogeographic studies focus only on islands' physical characteristics, we found evidence for an equivalent role of marine subsidy in structuring island bird communities. Our study suggests that for small islands, disentangling the effects of island biogeographic characteristics, marine inputs, and biotic interactions is a useful next step in understanding species distributions.

Can indicator species guide conservation investments to restore connectivity in Great Lakes tributaries? - Kimberly B. Fitzpatrick; Allison T. Moody; Austin Milt; Matthew E. Herbert; Mary Khoury; Eugene Yacobson; Jared A. Ross; Patrick J. Doran; Michael C. Ferris; Peter B. McIntyre; Thomas M. Neeson (Biodiversity and Conservation, 2021)

Comparison of bonobo and chimpanzee brain microstructure reveals differences in socio-emotional circuits - Habon A. Issa; Nicky Staes; Sophia Diggs-Galligan; Cheryl D. Stimpson; Annette Gendron-Fitzpatrick; Jared P. Taglialatela; Patrick R. Hof; William D. Hopkins; Chet C. Sherwood (Brain Structure and Function, 2019)

Correction to: Evaluation of a synthetic rainfall model, P-CLIPER, for use in coastal flood modeling - Kevin M. Geoghegan; Patrick Fitzpatrick; Randall L. Kolar; Kendra M. Dresback (Natural Hazards, 2018)

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

Conserving rare species can have high opportunity costs for common species - Thomas M. Neeson; Patrick J. Doran; Michael C. Ferris; Kimberly B. Fitzpatrick; Matthew Herbert; Mary Khoury; Allison T. Moody; Jared Ross; Eugene Yacobson; Peter B. McIntyre (Global Change Biology, 2018)
Conservation practitioners face difficult choices in apportioning limited resources between rare species (to ensure their existence) and common species (to ensure their abundance and ecosystem contributions). We quantified the opportunity costs of conserving rare species of migratory fishes in the context of removing dams and retrofitting road culverts across 1,883 tributaries of the North American Great Lakes. Our optimization models show that maximizing total habitat gains across species can be very efficient in terms of benefits achieved per dollar spent, but disproportionately benefits common species. Conservation approaches that target rare species, or that ensure some benefits for every species (i.e., complementarity) enable strategic allocation of resources among species but reduce aggregate habitat gains. Thus, small habitat gains for the rarest species necessarily come at the expense of more than 20 times as much habitat for common ones. These opportunity costs are likely to occur in many ecosystems because range limits and conservation costs often vary widely among species. Given that common species worldwide are declining more rapidly than rare ones within major taxa, our findings provide incentive for triage among multiple worthy conservation targets.

Evaluation of a synthetic rainfall model, P-CLIPER, for use in coastal flood modeling - Kevin M. Geoghegan; Patrick Fitzpatrick; Randall L. Kolar; Kendra M. Dresback (Natural Hazards, 2018)

Initial evaluations of a Gulf of Mexico/Caribbean ocean forecast system in the context of the Deepwater Horizon disaster - Edward D. Zaron; Patrick J. Fitzpatrick; Scott L. Cross; John M. Harding; Frank L. Bub; Jerry D. Wiggert; Dong S. Ko; Yee Lau; Katharine Woodard; Christopher N. K. Mooers (Frontiers of Earth Science, 2015)

Coping with aquatic hypoxia: how the plainfin midshipman (Porichthys notatus) tolerates the intertidal zone - Paul M. Craig; John L. Fitzpatrick; Patrick J. Walsh; Chris M. Wood; Grant B. McClelland (Environmental Biology of Fishes, 2014)

Clinical and molecular genetic features of ARC syndrome - Paul Gissen; Louise Tee; Colin A. Johnson; Emmanuelle Genin; Almuth Caliebe; David Chitayat; Carol Clericuzio; Jonas Denecke; Maja Di Rocco; Björn Fischler; David FitzPatrick; Angeles García-Cazorla; et al. (Human Genetics, 2006)